Analisis Pengungkapan Corporate Social Responsibility Perbankan Syariah Indonesia Berdasarkan Islamic Social Reporting Index - Sawitri, Desy Retma; Juanda, Ahmad; Jati, A Waluya (Kompartemen : Jurnal Ilmiah Akuntansi, 2017)
The purpose of this research is to evaluate the data shown by Corporate Social Responsibility at shareea banks in Indonesia, which analyzed by ISR index. This research used a sampling method. The samples which are used for the purpose of this research are the purposive sampling taken from shareea banks at Indonesia which already registered on 2015 and 2016. The result of this research showed that Indonesia Muamalat Bank scored the highest at CSR at 86% and disclosed consistently, while Victoria Bank of Indonesia scored the lowest at 54%. The data also showed that there were four shareea banks which ranked as very informative, they were: Indonesia Muamalat Bank, Shareea Bank of Indonesia Nation, Mandiri Shareea Bank, and Central Asia Bank. There were also five shareea banks which simply ranked informative, they were: Mega Shareea Bank, Shareea Bank of Indonesia Citizen, Bukopin Shareea Bank, Shareea Bank of Banten of West Java and Panin Shareea Bank. Last, there were two banks which are evaluated as less informative namely Shareea Bank of Maybank Indonesia and Victoria Shareea Bank. Keywords: Corporate Social Responsibility, Shareea Banks, ISR index.